Some basic US conditions for a law of the sea treaty - W. J. Feuerlein (Intereconomics, 1978)
Already in 1972 legislation for the exploration and subsequent exploitation of the resources of the deep ocean bed was first introduced in the USA. However, action was postponed each year in order to give the UN Law of the Sea Conference an opportunity to come forth with an acceptable treaty draft. This attitude changed drastically since the Sixth Session of the Conference in 1977. Professor Feuerlein explains the present US position and its background.
Keywords: 330; Law Of The Sea